Pengaruh Penerapan E-Audit Dan Etika Auditor Terhadap Kualitas Audit Dengan Auditor Fee Sebagai Pemoderasi - abidah ardelia, vania belva; Lidia Wahyuni; Nurhafifah Amalina (PT. Cendekia Sapta Indonesia, 2026)
This study examines the influence of e-audit, auditor ethics, and auditor fee on audit quality, as well as the role of auditor fee as a moderating variable. Through a quantitative research method with a 1-5 Likert scale questionnaire on 96 auditors working at Public Accounting Firms (KAP) in DKI Jakarta Province selected through convenience sampling and calculated using the Cochran formula, data were collected for descriptive and inferential analysis using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) version 3 application. The results show that e-audit, auditor ethics, and auditor fee individually have a positive and significant effect on audit quality. However, auditor fee negatively moderate the relationship between e-audit and audit quality, reflecting that cost pressures can hinder the optimization of digital audit technology. Conversely, auditor fee strengthen the influence of auditor ethics on audit quality, confirming the importance of adequate compensation in maintaining auditor integrity and professionalism. The practical implications of this study emphasize the need for strategic investment in digital audit technology training, proportional adjustment of fee structures, strengthening the culture of professional ethics through certification, supervision, and training to maintain more reliable and accountable audit quality.